Characteristics of reproductive performance of Garut rams - Muhammad Rizal; M.R Toelihere; T.L Yusuf; B Purwantara; P Situmorang (Indonesian Center for Animal Research and Development (ICARD), 2003)
Basic information on reproductive potency of Garut rams is necessary in order to identify the capacity of rams in producing chilled or frozen semen. Eight Garut rams (three to five years old) were used in this study. The male sexual behaviors were observed and semen was collected once a week using artificial vagina. Semen quality was evaluated and its potency to produce frozen semen was calculated. Results of this study indicated that first, second, and third ejaculations were at the 29, 87 and 176th seconds, respectively. Fresh semen volume, sperm concentration, motility, intact acrosomal cap, and intact plasma membrane were 0.99 ml, 3224 million/ml; 76.67; 86.13 and 87.73%, respectively. Protein value, fructose, vitamin C, vitamin E, sodiu, potassium, calcium, magnesium, phosphor, chloride, and mangan in seminal plasma of fresh semen were 4140, 180, 3.2, 24, 180, 117, 9, 6.12, 60, 104, and 5 mg/ml, respectively. Measurement of head length, width, and length of sperm tail were 6.59, 3.99, and 42.65 μm, respectively. Length and width measurement of right and left testes, and scrotal circumference were 12.71, 6.5, and 32.36 cm, respectively. Capacity of each Garut rams to produce frozen semen from three consecutive ejaculations are 35.88 mini straw with the cencentration of 200 million motile sperm per 0.25 ml. Key words: Reproductive characteristics, Garut rams